Mindfulness affecting loyalty with mediating role of customer experience in the context of adventure tourism in Vietnam - Nguyen Ngoc Quang; Dao Cam Thuy (Cogent Social Sciences)
Mindfulness is a concept that has been studied both in the East and in the West, which can be understood simply as a state of attention and response to stimuli. In the particular context of the travelling industry, mindfulness will raise customer-focused attention (FAT) and involvement in activities they participate in or in the services they receive. This research was conducted to test a model of mindfulness affecting loyalty (return intention and word of mouth) with the mediating role of customer experience. Quantitative analysis was performed with questionnaires from 388 respondents who are experiencing adventure tourism in Vietnam with 15 travel agents. The result shows that (1) Novelty producing (NOP), novelty seeking (NOS) and FAT have significant contributions to Mindfulness (2) Mindfulness has a positive effect on customer experience, return intention and word of mouth (3) Customer experience both has a direct impact and acts as an intermediary factor affecting return intention and word of mouth. The findings contribute academically to testing the mindfulness scale and the causal relationship between this factor and customer loyalty. It also allows the managers to improve overall customer loyalty through a better understanding of its dimensions.